Display of the antigenic region of Nipah virus nucleocapsid protein on hepatitis B virus capsid - Yap, Wei Boon; Tey, Beng Ti; Mohammed Alitheen, Noorjahan Banu; Tan, Wen Siang (The Society for Biotechnology, Japan, 2012)
The C-terminal domain of Nipah virus (NiV) nucleocapsid protein (NP 401-532) was inserted at the N-terminus and the immunodominant loop of hepatitis B core antigen (HBc). The stability of NP 401-532 increased tremendously when displayed on the HBc particles. These particles reacted specifically with the swine anti-NiV and the human anti-HBc antisera.